Investigating the Effectiveness of Livability Indicators Using the Partial Least Squares Approach; Case study: Central part of Bojnord city - foroogh khazaee nezhad; sakine beigi (تحقیقات کاربردی علوم جغرافیایی)
Today, most of the world's population lives in cities, and urbanization, as the dominant phenomenon of human life, has continued to grow. But in recent years, the lives of city dwellers have faced many problems. In recent years, urban experts are looking for a solution for these problems, in which different theories, views, approaches, and models have been proposed. One of the most important approaches is the livability that is related to sustainable development. In this study, the relationship between different indicators of livability and its nature is explained. The central part of Bojnourd city has been selected as the case study. This research is a practical, desk and field study. Structural Equation Modeling with partial least squares approach and related software were used for data analysis. The results of the research showed that although there is a significant relationship between most of the indicators studied in this study and the viability, the local participation, educational facilities, and leisure facilities have had the greatest impact on livability. It was also found that there is a significant statistical relationship between residence time and identity (P = 0.01) and duration of residence and individual participation (P = 0.08) (90% confidence level).